2014
DOI: 10.4103/1119-3077.122847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the topical hemostatic agent Ankaferd Blood Stopper on the incidence of alveolar osteitis after surgical removal of an impacted mandibular third molar

Abstract: The results showed that ABS administration did not increase the incidence of AO formation. Thus, ABS can be used safely for hemostasis after impacted mandibular third molar surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…The proteomics of the structural and functional properties of the proteins related to the wound healing should also be matched with the already established proteomics of ABS [41]. Experimental trials indicated that ABS is effective in wound healing [39,42,43,44,45,46,47]. The results of our present study disclosed that ABS has antimicrobial effects against bacteria that are active in wound and burn complications.…”
Section: Discussionmentioning
confidence: 54%
“…The proteomics of the structural and functional properties of the proteins related to the wound healing should also be matched with the already established proteomics of ABS [41]. Experimental trials indicated that ABS is effective in wound healing [39,42,43,44,45,46,47]. The results of our present study disclosed that ABS has antimicrobial effects against bacteria that are active in wound and burn complications.…”
Section: Discussionmentioning
confidence: 54%
“…Alveolar osteitis is a common complication after extraction of impacted mandibular third molars. The incidence varies from 0 to 45%. The treatment method used to manage the alveolar osteitis in this study was emphasised in an earlier study to be reliable in the management of this condition.…”
Section: Discussionmentioning
confidence: 96%
“…In another study which was conducted by 25 patients who were undergone bronchoscopy procedure, ABS has successfully controlled the bleeding episodes of the cases (Uzun et al 2014). There are three different clinical studies which confirms ABS as a successful hemostatic agent that was conducted with 25, 50 and 113 patients, respectively (Kazancıoğlu et al 2013; Tek et al 2014; Beyazit et al 2011). ABS could also be used in gynecological cases.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of ABS in numerous systems had been demonstrated in the literature. For instance; ABS is very effective in the controlling of hemorrhages within the gingival tissue (Amer et al 2014), lung tissue (Uzun et al 2014), tooth extraction (Kazancıoğlu et al 2013; Tek et al 2014; Beyazit et al 2011), perineal tissue (Eyi et al 2013), oral mucosa tissue (Leblebisatan et al 2012), gastrointestinal tissue (Karaman et al 2012), thyroid tissue (Guler et al 2011), nasopharyngeal tissue (Iynen et al 2011; Yasar and Ozkul 2011), nasal tissue (Teker et al 2010), peritonsillary tissue (Teker et al 2009). Also, it has been reported that partial nephrectomy operation in human was performed without any complication with ABS (Huri et al 2010).…”
Section: Introductionmentioning
confidence: 99%